The Human rights committee and the presumption of innocence: An extraprocedural right? - Hidalgo Flores, Héctor Ivar (2020)
The Human Rights Committee has issued several legal opinions wherein it has analyzed the right to the presumption of innocence.  This United Nations body has unraveled the scope of this guarantee and, certainly, has brought to surface its multifaceted character.  However, much of its jurisprudence has focused on the extra-procedural aspect of this right.  Therefore, as the working hypothesis, it was formulated that the right to the presumption of innocence, from the interpretation of the Human Rights Committee, was a purely extra-procedural guarantee.  However, the investigation showed that although its jurisprudence has been characterized by conceiving this principle as a right that comes to life outside the legal process, it also contains other criteria that extend the scope of this legal institution.